Bipolar Disorder in Jenniver Niven’s All The Bright Places - Budiani, Rachma; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study is entitled Bipolar Disorder in Jennifer Niven’s All The Bright Places which discusses the bipolar disorder experienced by a teenage boy named Theodore Finch, who is the main character. It focuses on the symptoms, causes, and effects of bipolar disorder. This thesis applies qualitative descriptive method, combined with a psychological approach due to its relevance to the topic of bipolar disorder. The analysis shows that the symptoms of bipolar disorder consist of manic, depressive, and mixed episodes. Finch experiences all three episodes persistently. The causes of his bipolar disorder are linked to psychological factors, such as childhood trauma caused by his abusive father, and environmental factors, such as bullying from his schoolmates. Finch’s condition worsens due to the absence of proper therapy, leading him to misuse pills as a coping mechanism. Theodore Finch’s struggle with bipolar disorder illustrates the profound impact of mental illness on both individuals and those around them. Bipolar disorder significantly affects Finch’s life, ultimately leading to his tragic death.